1999
DOI: 10.1080/00288330.1999.9516862
|View full text |Cite
|
Sign up to set email alerts
|

Animal and human faecal pollution in New Zealand rivers

Abstract: Sentinel freshwater mussels (Hydridella menziesi) were immersed in rivers at sites impacted by faecal pollution. The indicator bacterium, Escherichia coli, was recovered from all mussels including those at a forest control site, but concentrations were highest at sites impacted by either treated sewage or treated meat-processing waste water, or by inputs from dairy farms. The three pathogens sought were recovered from mussels, except those at the forest (control) site: Campylobacter jejuni and Campylobacter co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…Campylobacter spp. have been isolated from rivers impacted by pastoral farming and by point-source discharges of sewage and meat processing wastewaters (Donnison & Ross 1999) and there was a 60% recovery rate of thermotolerant campylobacters over two years at 25 freshwater beaches (Savill et al 2001). Epidemiological quantitative microbial risk assessment suggests that about 5% of New Zealand's cases of campylobacteriosis can be attributed to contact recreation in freshwater (Till et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter spp. have been isolated from rivers impacted by pastoral farming and by point-source discharges of sewage and meat processing wastewaters (Donnison & Ross 1999) and there was a 60% recovery rate of thermotolerant campylobacters over two years at 25 freshwater beaches (Savill et al 2001). Epidemiological quantitative microbial risk assessment suggests that about 5% of New Zealand's cases of campylobacteriosis can be attributed to contact recreation in freshwater (Till et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While there is significant evidence of the direct impact of cattle on rural waterways (6,9,11,31), sheep have nevertheless been implicated as contributors to bacterial indicator and pathogen loadings in rivers and streams (8,10,18,20). It has been suggested that the total number of Escherichia coli per hectare of pasture are higher for sheep than for cattle (30).…”
mentioning
confidence: 99%
“…They exhibit most characteristics of "sentinel organisms" (Phillips and Rainbow 1992), and potentially are biomonitors of ecosystem health (Jeffree et al 1995a). In New Zealand, for example, Hyridella menziesi has proven effective as a sentinel for bacteria and viruses in waters exposed to faecal pollution (Donnison and Ross 1999). Reproductive responses also may have biomonitoring applications (e.g.…”
Section: Biomonitoringmentioning
confidence: 99%